Implementation and outcomes of an urban mobile adult extracorporeal life support programCentral MessagePerspective - Joseph Hadaya, MD; Yas Sanaiha, MD; Vadim Gudzenko, MD; Nida Qadir, MD; Sumit Singh, MD; Ali Nsair, MD; Nam Yong Cho, BS; Richard J. Shemin, MD; Peyman Benharash, MD; Ida Anderson; Stephanie Bland; David Boldt; et al. (JTCVS Techniques)
Objective: Although extracorporeal life support (ECLS) has been increasingly adopted as rescue therapy for cardiac and pulmonary failure, it remains limited to specialized centers. The present study reports our institutional experience with mobile ECLS across broad indications, including postcardiotomy syndrome, cardiogenic shock, and COVID-19 acute respiratory failure. Methods: We performed a retrospective review of all patients transported to our institution through our mobile ECLS program from January 1, 2018, to January 15, 2021. Results: Of 110 patients transported to our institution on ECLS, 65.5% required venovenous, 30.9% peripheral venoarterial, and 3.6% central venoarterial support. The most common indications for mobile ECLS were acute respiratory failure (46.4%), COVID–19-associated respiratory failure (19.1%), cardiogenic shock (18.2%) and postcardiotomy syndrome (11.8%). The median pre-ECLS Pao2:Fio2 for venovenous-ECLS was 64 mm Hg (interquartile range [IQR], 53-75 mm Hg) and 95.8 mm Hg (IQR, 55-227 mm Hg) for venoarterial-ECLS, whereas median pH and base deficit were 7.25 (IQR, 7.16-7.33) and 7 mmol/L (IQR, 4-11 mmol/L) for those requiring venoarterial-ECLS. Patients were transported using a ground ambulance from 50 institutions with a median distance of 27.5 miles (IQR, 18.7-48.0 miles). Extracorporeal circulation was established within a median of 45 minutes (IQR, 30-55 minutes) after team arrival. Survival to discharge was 67.3% for those requiring venovenous-ECLS for non–COVID-19 respiratory failure, 52.4% for those with COVID-19%, and 54.1% for those requiring venoarterial-ECLS. Conclusions: Patients can be safely and expeditiously placed on ECLS across broad indications, utilizing ground transportation in an urban setting. Clinical outcomes are promising and comparable to institutional non-transfers and those reported by Extracorporeal Life Support Organization.